Regulation of Histone Methylation and Reprogramming of Gene Expression in the Rice Inflorescence Meristem. Issue 5 (8th May 2015) - Liu, Xiaoyun; Zhou, Shaoli; Wang, Wentao; Ye, Yiran; Zhao, Yu; Xu, Qiutao; Zhou, Chao; Tan, Feng; Cheng, Saifeng; Zhou, Dao-Xiu
Abstract : Comparison of the inflorescence and shoot apical meristems reveals differences in gene expression and H3K27me3/H3K4me3 ratio and overexpression of a key methylase increases inflorescence meristem activity and panicle size. Abstract: Rice inflorescence meristem (IM ) activity is essential for panicle development and grain production. How chromatin and epigenetic mechanisms regulate IM activity remains unclear. Genome-wide analysis revealed that in addition to genes involved in the vegetative to reproductive transition, many metabolic and protein synthetic genes were activated in IM compared with shoot apical meristem and that a change in the H3K27me3/H3K4me3 ratio was an important factor for the differential expression of many genes. Thousands of genes gained or lost H3K27me3 in IM, and downregulation of the H3K27 methyltransferase gene SET DOMAIN GROUP 711 ( SDG711 ) or mutation of the H3K4 demethylase gene JMJ703 eliminated the increase of H3K27me3 in many genes. SDG711 -mediated H3K27me3 repressed several important genes involved in IM activity and many genes that are silent in the IM but activated during floral organogenesis or other developmental stages. SDG711 overexpression augmented IM activity and increased panicle size; suppression of SDG711 by RNA interference had the opposite effect. Double knockdown/knockout of SDG711 and JMJ703 further reduced panicle size. These results suggest that SDG711 and JMJ703 have agonistic functions in reprogramming the H3K27me3/H3K4me3 ratio and modulating gene expression in the IM .